Analisis kemampuan pemecahan masalah numerasi siswa berdasarkan tahapan polya ditinjau dari gaya belajar - Fauziyah, Nur; Anam, Ainul; Aslikhatin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This research aims to describe students' numeracy problem-solving abilities based on the Polya stages in terms of learning styles. The subjects of this research were 3 female students, namely 1 student with a high-ability visual learning style, 1 student with a high-ability auditory learning style, and 1 student with a high-ability kinesthetic learning style. Data collection techniques include conducting tests and semi-structured interviews. Data analysis includes data reduction, data presentation, and conclusion. The research results obtained were that subjects with an auditory learning style had better abilities compared to subjects with a visual learning style and a kinesthetic learning style. Subjects with an auditory learning style have good problem-solving abilities at all stages of Polya. Meanwhile, subjects with a visual learning style have good problem-solving abilities in understanding problems and making plans even though they are incomplete in writing down information. Then subjects with a kinesthetic learning style have good problem-solving abilities at all stages of Polya even though the subjects are incomplete in writing down information at the stage of understanding the problem and making plans.